THE DEVELOPMENT OF COLESTVIAMODEL AS AN EFFORT OF INTERNANALIZATION OF CHARACTER VALUES IN SOCIAL STUDIES - Agung S, Leo (Dewantara, 2013)
Purpose: This research is based on a condition of Social Studies instruction in Junior High schools in Surakarta that is still far from the expectation. It focuses on the cognitive aspect and lack of affective aspects. Therefore, it is important to develop an instruction throughCOLESTVIA Model by combining STAD type, Tournament and VIA as an effort in internalization of character values in Social Studies instruction. The development of character values is concerned with cognitive development and the result of social interaction. It is believed that by integrating the character values, it can strengthen the character and personality for the Junior High school students in Surakarta. Method:The Developmentof COLESTVIA Model is done through development research by three main steps, namely Preliminary Study, Development, and Model Pilot. The data was collected through Observational Technique, Interview, Questionaire and Doccumentation. The Data Analysis for the Preliminary Study uses qualitative, while the Model Pilot was by means of experiment using quantitative Approach as to answer the research questions, namely : (1) How is the performance of the Social Studies instruction of the grade VIII of Junior High School students in Surakarta, (2) How is the development of COLESTVIA Model that can integrate the character values, and (3) How is the effectiveness of The DevelopmentCOLESTVIA Model as an attempt of the internalization of the character values in Social Studies instruction in grade VIII Junior High school.T-test was used to know the difference between the model of COLESTVIA instruction and conventional model. Findings: The result of the research shows after performing the try out in SMP 19 through Classroom Action Research (CAR); the larger scaled-trial in SMP 2 and private Junior High School A, (experiment), SMP 3 and private Junior High School B (control), and the effectiveness of trial in SMP 19, SMP 24 and private Junior High School C (experiment) and SMP 10, SMP 25 and private Junior High School D (contol), proved that thatCOLESTVIA instruction is able to improve the competency and the SMP students? character values in various groups of schools. The conclusion of the research is that the model of COLESTVIA instruction fulfill the principles and proves significantly the increase of the SMP students? character values in Surakarta compared with the various conventional models of instruction. Keywords : Social studies,learning models, competency, character values, and personality.